3D Technological System of Management of Geological Exploration Processes of Mining Enterprises - Ravshanov Zavqiddin Yahyo Oʻgʻli; Ergasheva Zulxumor Abdaaliyevna; Maxsitaliyeva Lolaxon Olimjon qizi; Pardaev Shohrux Shovkat oʻgʻli; O‘telbayev Azizbek Alisher o‘g‘li (International Journal on Integrated Education, 2022)
3D modeling technique has become a favorable tool for people to observe and analyze the world, and has been used widely in various trades. Geological body enrich mineral resources, and the spatial shape and petrophysical distributions of geological body are controlled by geological conditions. So 3D geological modeling under the control of complex geological conditions becomes the research emphasis. This article analyzes the uncertainty, complexity and diversity of geological body, and lists complex geological conditions controlling spatial shape and petrophysical distributions of geological body. And then 3D geological modeling method under the control of complex geological conditions is proposed, and corresponding modeling workflow is set up.